Precedented environmental futures : skin and substance - Porteous, Colin (Cambridge Scholars Publishing, 2019)
This book addresses the built environment through the lens of environmental architecture, and in a holistic manner. It moves gradually from psychophysiology and thinking-doing-feeling modalities, through environmental criteria to environmental modulation, concluding with a debate around mitigation and adaptation. Much use is made of re-interpreting past quotations seen as relevant for environmental architecture. No definitive conclusions are reached, but rather broad discursive messages are offered. The text will have lasting luminance for new generations involved with the built environment.